(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the latest developments in smart devices and services and their impact on the digital economy. It briefly reviews advancements in areas such as Internet of Things (IoT) technologies, artificial intelligence, automated applications, and smart devices and services. These technologies play a significant role in improving energy efficiency, data analysis, management and monitoring processes, and in providing efficient services in areas like smart homes and cities.